ANALISIS PARAMETER FISIKA TERHADAP PENGENDALIAN TEKANAN LUMPUR PENGEBORAN STUDI KASUS: PREVENSI KICK DAN BLOWOUT - Wenny Wahyuni; Lilik Hendrajaya (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
In the drilling proses mud drilling in use, type of drill bit, casing and cementing is a matter that must be considered. Mud drilling injected into the drill pipe must be adapted to conditions existing rock formations below ground level, where the pressure of the mud drilling (hidrostatik pressure) must be greater than the formation pressure. Hidrostatik pressure associated with a mud weight, it can be analyzed using hydrostatic equation. If the control hidrostatik pressure in the annulus can not be maintained properly and the formation pressure exceeds the pressure of the drilling mud, as shown by the difference in pressure value mud injected and were out past the annulus is not equal to zero (P â‰  0) then the formation fluid will rise to the surface. According to research that has been carried, the flow of formation fluid in the drilling of occurred at depths of 565, 577 and 797 ft caused due to loss circulation of mud, the flow of formation fluids regarded as a kick, if the kick can not be resolved then it will result in blowout.Keywords: Kick, loss circulation, hidrostatik pressure, pore pressures.